Reg Anning interviewed by Bob Rummery for the Bob Rummery collection of Folklore and Social History recordings - Anning, Reg, 1913-; Rummery, Bob. (1994)
Mr Anning speaks of his family's migration to Western Australia in 1924 as part of the Devon and Cornwall Group 116; his parents' decision to migrate; preparations for sailing; the merchant ship; meeting the other Group Settlers; boarding the SS Themistocles; leaving Plymouth; re-coaling at Cape Town; Mrs Shepherd as a spiritualist; child breaking his leg; arrival at Albany; car trip from Denmark; settlers' shacks; sitting around the log fire on the first night; lack of a school; working for his father clearing for the Group; Walpole Group; hardships during the Depression; dances; music; beer; Paddy Cochrane from Hazelvale; accordion playing; travelling to dances; Harry Packer playing the accordion upside down; learning to play the accordion; Lew Hunter's Grand Organ; playing for his first dance; playing drums in the Five Ace band; the Ministrels; vote to decide which band to have at a dance; his drum set; his playing tunes by ear.
Recorded at Pemberton, Western Australia.
Transcript available: (19 leaves)
Keywords: Anning, Reg -- Interviews; Foresters -- Western Australia -- Pemberton -- Interviews; Immigrants -- Western Australia -- Pemberton